29.8k views
5 votes
In the equation 6x − 2 = −4x + 2, Spencer claims that the first step is to add 4x to both sides. Jeremiah claims that the first step is to subtract 6x from both sides. Who is correct? Explain. i dont need an answer thats just an example i just wanna know how you would choose which to do first because it seems like it would be the same either way

User Ruehri
by
5.0k points

1 Answer

2 votes

Answer:


x=(2)/(5)

Explanation:


6x-2+2=-4x+2+2\\\\6x=-4x+4\\6x+4x=-4x+4+4x\\10x=4\\


(10x)/(10)=(4)/(10)\\\\x=(2)/(5)

User Halis
by
4.9k points